Diatom data of sediment core MD07-3081 - Elisabeth Teca; Elisabeth Michel; Giuseppe Siani; Xavier Crosta; Carina Beatriz Lange; Consuelo Martínez Fontaine; Paola Cárdenas (PANGAEA, 2025)
This dataset contains diatom abundance (Valves g-1), fragments (%), and relative percentage of diatom species and associated standard error (%) from core MD07-3081. 51 samples, with a resolution of 0.1 to 1 ka, were analyzed for diatom content. For sediment processing and slide preparation, we followed the protocol described by Crosta et al., 2020. We calculated the associated error of each percentage based on the equation proposed by Patterson and Fishbein (1989). Chaetoceros spp. resting spores (CRS) were not identified at the species level. Due to their similar ecology, we grouped the species Thalassionema nitzschioides var. capitulata and Thalassionema nitzschioides var. lanceolata under the Thalassionema nitzschioides group, the species Shionodiscus trifultus and Shionodiscus frenguellii were grouped under the name of the Shionodiscus group because these species look very similar under the light microscope and have a similar ecology and distribution in subantarctic waters, Azpeitia tabularis var. tabularis and Azpeitia tabularis var. egrerius were combined into the Azpeitia tabularis group. Finally, Shionodiscus oestrupii var. oestrupii is referred hereafter to Shionodiscus oestrupii. Total diatom counts include Chaetoceros resting spores.
In: Teca, E et al. (2025): Geological investigations on sediment core MD07-3081 [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.974782